Perkembangan Pasa Ateh (Pasar Atas) Bukittinggi Hingga Menjadi Plaza Tahun 2017-2023 - Ramadhan, Mutiara Yulia; Asri, Zul (Jurnal Kronologi, 2023)
In the research talk about the development of Pasa Ateh (Upper Market) Bukittinggi after it experienced a fire and became a plaza (2017-2023). Of this study focusses about discusses the physical development of the Pasa Ateh (Upper Market) Bukittinggi building after the fire until it became a plaza and explains the economic and social impact of traders caused by the revitalization of the market building after the fire. The aim of this research is to see the development of Pasa Ateh (Upper Market) Bukittinggi after the fire until it became a plaza and see the social and economic impact caused by the revitalization of the market after the fire. This research includes qualitative historical research, using the historical method which includes 4 stages, namely: heuristic method by searching for historical data related to Pasa Ateh (Upper Market), source criticism in the form of selecting data that has been taken, interpretation in the form of interpreting historical data, and Historiography is the rewriting of History. From the first discussion, Pasa Ateh (Upper Market) Bukittinggi experienced a fire in 2017. Second, the development of Pasa Ateh (Upper Market) in terms of physical buildings. Third, the social and economic impacts resulting from the revitalization of buildings. Keywords: History, Development, Pasa Ateh (Upper Market), Social and Economic